2015
DOI: 10.1038/ngeo2592
|View full text |Cite
|
Sign up to set email alerts
|

Internal deformation of the subducted Nazca slab inferred from seismic anisotropy

Abstract: Within oceanic lithosphere a fossilised fabric is often preserved originating 15 from the time of plate formation. Such fabric is thought to form at the mid-ocean 16 ridge when olivine crystals align with the direction of plate spreading 1,2 . It is 17 unclear, however, whether this fossil fabric is preserved within slabs during 18 subduction or over-printed by subduction-induced deformation. The alignment of 19 olivine crystals, such as within fossil fabrics, can generate anisotropy that is sensed 20 by passi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
39
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 34 publications
13
39
1
Order By: Relevance
“…These splitting directions are similar to those observed to the south of our study area by Anderson et al [2004] and MacDougall et al [2012]. Eakin et al [2016] demonstrated that deformation along the edges of flat slabs can induce strong slab-internal anisotropy with trench-parallel orientations. The variable northeasternmost ESP stations do not lie directly updip from the slab tear.…”
Section: 1002/2017gl074312supporting
confidence: 91%
“…These splitting directions are similar to those observed to the south of our study area by Anderson et al [2004] and MacDougall et al [2012]. Eakin et al [2016] demonstrated that deformation along the edges of flat slabs can induce strong slab-internal anisotropy with trench-parallel orientations. The variable northeasternmost ESP stations do not lie directly updip from the slab tear.…”
Section: 1002/2017gl074312supporting
confidence: 91%
“…This lateral mantle flow may contribute to the low shear wave velocities we observe beneath the inboard easternmost corner of the flat slab. We find evidence for modified slab fabric along the southern edge of the flat slab, consistent with previous results and interpretations of Eakin et al [], but preserved fossil spreading fabric within the torn slab to the north. The contrast in slab fabric along the strike supports the hypothesis that the extension due to change in slab geometry from steep to flat may alter the internal slab anisotropy upon subduction.…”
Section: Introductionsupporting
confidence: 92%
“…The model for upper mantle anisotropy obtained in this study provides constraints complementary to those provided by shear wave splitting, which has previously been studied in this region by Eakin et al [, , ] and Long et al []. Here we briefly discuss the comparison between the two types of studies, illustrated in Figure .…”
Section: Discussionsupporting
confidence: 66%
“…In order to investigate variations in seismic anisotropy in the subducting Hikurangi slab we selected earthquakes that had a station–earthquake raypath that was approximately parallel to the dip of the subducting slab (∼300°). By doing this, the anisotropy measurements will originate from earthquake raypaths that sample large portions of the downgoing slab, as the fast internal velocities of the slab will act as a waveguide (Eakin et al, ). We confirm this behavior by comparing the S‐wave frequencies of these deep earthquakes at stations in the Hikurangi arc and in the NW of the North Island (Supporting information Figure S1).…”
Section: Resultsmentioning
confidence: 99%